Environment in 2005 Country Assistance Strategies - Kishore, Sunanda (World Bank, Washington, DC, 2014)
Country Assistance Strategies (CASs) have been periodically reviewed from a variety of different perspectives. This review assesses how environment is integrated in CASs for 2005 and also compares the progress made by 37 countries over the period of 1999-2005. Five themes are used to assess the 23 CASs across an established methodology also used in previous reviews. The five themes are: issues identification, treatment, mainstreaming, environmental policy and poverty- environment linkages. The review finds that the treatment of environment in CASs has only marginally improved. However, the positive aspect is the increase in the number of good practice cases as illustrated by high scores of individual countries under the five different themes. These good practice cases provide lessons and serve as tools for strengthening future CASs. Poverty environment linkages continue to remain the weakest aspect of CASs.